Unusual Dermoid Cyst in Oral Cavity - Evanice Menezes Marçal Vieira; Alvaro Henrique Borges; Luis Evaristo Ricci Volpato; Alessandra Nogueira Porto; Artur Aburad Carvalhosa; Gilberto de Almeida Botelho; Matheus Coelho Bandeca (Hindawi Limited, 2014)
Dermoid cysts in oral cavity are unusual lesions. Their etiology is not yet clear and can be associated with trapped cells as a result of the inclusion error resulting in the development into the ectoderm, mesoderm, and endoderm tissues. The aim of this case report is to evidence the presence of a dermoid cyst in the floor of mouth surgically removed. In the present case, the lesion showed soft consistency, floating, regular borders, smooth surface, and the same color as the adjacent mucosa, asymptomatic and measuring 4.5 × 5.5 cm in its greatest diameter. The initial diagnostic was ranula in consequence of the similarity with clinical characteristics and localization. After surgical removal lesion, a fibrotic capsule was identified with a friable material with intensive yellow color. The microscopic exam showed cystic lesion with cavity lined by squamous stratified epithelium hyperorthokeratinized. Cutaneous attachments, such as sebaceous glands and hair follicles, were present in connective adjacent tissue. Surgical intervention is elective in these situations. All dentists must have a thorough knowledge of this unusual lesion.